Integrated management of Bactericera cockerelli in potato crops in northern Peru: CIP experimental field, Huancabamba Province, Piura - Gamarra, H.; Correa, Y.; Peña, S.; Carhuapoma, Pablo; Pérez, W.; Huaman, E.; Kreuze, Jan F. (2025)
This report demonstrates that integrated potato psyllid management in northern Peru can benefit significantly from the use of biorational strategies, particularly the combination of Beauveria bassiana and Cordyceps javanica, which was the most effective for controlling eggs, nymphs, and adults. However, even under low vector populations, the presence of Candidatus Liberibacter solanacearum in tubers was confirmed, demonstrating the insect's high efficiency as a vector. This study aligns strongly with Regenerative Agriculture, Resilient Agrifood Systems, and Crop Protection, and constitutes a key input for the design of integrated pest management (IPM) strategies adapted to the agroecological conditions of the northern Andes of Peru.